Mental Fatigue in Soccer Game : Literature Review - Gaung Perwira Yustika (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2018)
Soccer is a sport-game that needs intermittent cognitive ability, the requirement is for making quick and accurate decision under dinamic environment in the soccer pitch. This endurance needs make soccer a sport that mentally fatigue, which the impact to decrement in performance to to combination of physical fatigue and mental. Previous study showed us that mental fatigue influenced physical capacity and technical performance of soccer players, this made more experienced soccer players was more accurate to take decision than the non experienced one.Mental Fatigue in fact can reduce ability of technical areas a player, one of them is passing accuracy. The Loughborough Soccer Passing Test (LSPT) can be used to measured technical aspect of soccer players that influenced by mental fatigue, compared between control group and mental fatigue group. And the result showed the penalty time done by longer time than control group.Then, the mental fatigue is also influenced the physical capability of a player. The measurement can be done by Yo-yo IR1 test. The publication that used this protocol measurement showed us that energy expenditure and distance that can be covered by players decreased in subject during mental fatigue. This made a hypotesis one that mental fatigue also impact on physical performance of a player.